Microplastics to Megafauna: A Comprehensive Review of Plastic Pollution's Cascading Effects on Marine Food Webs and Ecosystem Functioning (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Plastic pollution has emerged as one of the most pervasive and rapidly escalating environmental crises of the 21st century, profoundly impacting marine ecosystems globally. This comprehensive literature review synthesizes current scientific understanding of the cascading effects of plastic pollution, particularly focusing on microplastics, from their initial entry into marine environments to their far-reaching consequences for marine food webs and overall ecosystem functioning. The review explores the ubiquity of plastic debris, the mechanisms of microplastic ingestion and subsequent trophic transfer across diverse marine organisms, and the multifaceted physiological and behavioral impacts observed at individual organism levels. Furthermore, it delves into the complex disruptions plastic pollution instigates within marine food webs, including alterations in predator-prey dynamics, energy flow, and nutrient cycling, ultimately leading to potential shifts in community structure and biodiversity. The review also examines the broader implications for critical ecosystem services, highlighting the role of plastics as vectors for invasive species and pathogens. Finally, it identifies significant knowledge gaps and proposes future research directions essential for developing effective mitigation strategies and fostering the resilience of marine ecosystems in the face of this escalating anthropogenic threat.